How do reaction conditions affect the enantiopure synthesis of 2‐substituted‐1, 4‐benzodioxane derivatives?. Issue 7 (12th May 2018) - Straniero, Valentina; Casiraghi, Andrea; Fumagalli, Laura; Valoti, Ermanno
Abstract: Several biologically active compounds structurally include the enantiopure 2‐substituted‐1, 4‐benzodioxane scaffold. The straightforward racemization that affects reactions involving most of the common chemical reactives is thus a crucial issue. The developing of a completely stereo‐controlled synthetic route that does not affect the enantiomeric excess is consequently mandatory. It is also important to set up a reliable chiral HPLC method, able to follow the reaction, and to improve the synthetic performances. Here, we report the chiral investigation of two different synthons, we specifically evaluated the synthetic pathways that could be run in order to afford them, avoiding the racemization processes, which could normally occur in basic conditions. In addition, we developed peculiar chiral HPLC methods in order to resolve the enantiomers, define the enantiomeric excess, and fully characterize these compounds. Abstract :